High-bending-resistance, high-medium-resistance and high-weather-resistance water-based fireproof coating as well as preparation method and application thereof
By optimizing the composition and treatment technology of water-based cable fire-resistant coatings, the problem of insufficient resistance of existing water-based coatings in harsh environments is solved, high bending resistance, medium solvent resistance and weather resistance are achieved, and hard carbonized layers are formed, which improves fire resistance performance. and service life, meet environmental protection requirements.
Patent Information
- Application Number
- CN202411342896.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing water-based cable fire-retardant coatings have insufficient salt water resistance, oil resistance, moisture and heat resistance and freeze-thaw resistance in harsh environments, resulting in cracking, swelling, and shedding problems, which are difficult to compare with solvent-based coatings, and their fire resistance and resistance are Poor expansion effect.
Use water-based fire-retardant coatings composed of water, aqueous emulsion, defoaming agent, dispersing agent, PH regulator, thickener, bactericide, film-forming additive, expansion flame retardant and refractory filler to efficiently disperse and grind Treatment to form highly bending, medium solvent resistant and weather-resistant coatings, combining zinc oxide and plasticizer to improve performance.
It significantly improves the oil resistance, salt water resistance, bending resistance and fire resistance of the coating, forms a hard carbonized layer, enhances the expansion effect and service life, meets environmental protection requirements, and exceeds the GB 28374-2012 standard.
Smart Images

Figure BDA0005060203400000061 
Figure BDA0005060203400000062 
Figure BDA0005060203400000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fire retardant coatings, and specifically relates to a water-based fire retardant coating and a preparation method and application thereof. Background Art
[0002] With the rapid development of the construction industry, fire safety has become an indispensable part of building design and construction. Among many fireproof materials, fireproof coatings have been widely used due to their simple construction and relatively low cost. Intumescent fireproof coatings, in particular, have important applications in fire protection fields such as cables and steel structures because they can quickly expand under fire conditions to form a heat-insulating protective layer, effectively delaying the spread of fire and reducing heat transfer.
[0003] However, traditional intumescent fire retardant coatings mostly use solvents as the medium, which poses environmental pollution and health risks. With the increasingly stringent environmental regulations and the improvement of public environmental awareness, the development of environmentally friendly water-based fire retardant coatings has become an inevitable trend in the development of the industry.
[0004] At present, water-based cable fire retardant coatings use water as solvent or dispersion medium, and have the advantages of low volatile organic compound (VOC) emission, non-flammability, and non-toxicity. However, in terms of fire retardant performance, it is often difficult to compare with solvent-based coatings, especially in terms of expansion effect, carbon layer quality, and durability.
[0005] In view of the harsh environment in which power cable facilities are laid, especially in some cable trenches where high temperature and high humidity occur all year round, most water-based cable fire retardant coatings on the market fail due to cracking, swelling, and falling off during application. Therefore, for products used in such harsh environments, their salt water resistance, oil resistance, moisture and heat resistance, and freeze-thaw cycle resistance are important indicators for evaluating their performance.
[0006] The quality of cable fire retardant coatings on the market is uneven. According to feedback from market applications, the main defects are as follows: (1) Poor salt water and oil resistance, with bulging and cracking occurring within 24 hours of immersion; (2) Poor bending resistance, prone to cracking and falling off; (3) Poor fire resistance, with the carbonized layer produced under high temperature easily powdering and lacking strength, and some even lacking expansion; (4) Poor weather resistance, with cracking and falling off occurring within a short period of time during outdoor use. Summary of the invention
[0007] In view of the technical problems of existing products, the present invention aims to provide a water-based fire-retardant coating with high bending resistance, high resistance to medium solvents, and high weather resistance. The product not only has excellent fireproof performance, including high expansion ratio, good carbon layer quality and strong thermal insulation effect, but also has the advantages of environmental protection, simple construction, and low cost. The present invention also relates to a method for preparing the water-based fire-retardant coating, which can ensure the stability and construction performance of the coating and meet the needs of modern construction and power fire protection. The present invention provides the following technical solutions:
[0008] A water-based fire retardant coating is made from the following raw material components:
[0009] 25-35 parts water
[0010] 15-30 parts of water-based emulsion
[0011] Defoaming agent 0.1~1 part
[0012] Dispersant 0.1~0.5 parts
[0013] PH regulator 0.01~1 part
[0014] Thickener 0.1~0.5 parts
[0015] Fungicide 0.01~1 part
[0016] Film-forming aid 0.1-2 parts
[0017] Intumescent flame retardant 25-40 parts
[0018] Refractory filler 5-15 parts
[0019] Zinc oxide 1-5 parts
[0020] Plasticizer 0.1 to 2 parts.
[0021] The water-based fire retardant coating according to the present invention is made from the following raw material components:
[0022] 28-32 parts water
[0023] 20-25 parts of water-based emulsion
[0024] Defoaming agent 0.3~0.7 parts
[0025] Dispersant 0.1~0.5 parts
[0026] PH regulator 0.08~0.2 parts
[0027] Thickener 0.1~0.3 parts
[0028] 0.08~0.5 parts of fungicide
[0029] Film-forming aid 0.5-1.5 parts
[0030] 30-40 parts of intumescent flame retardant
[0031] Refractory filler 6-10 parts
[0032] Zinc oxide 1-5 parts
[0033] Plasticizer 0.1 to 2 parts.
[0034] According to the water-based fire retardant coating of the present invention, wherein:
[0035] The water used is deionized water.
[0036] The aqueous emulsion is a vinyl acetate-ethylene copolymer emulsion, preferably a vinyl acetate-ethylene copolymer emulsion having a vinyl acetate (VA) content of 89% to 95%, a solid content of 54% to 56%, and a viscosity of 2700 to 5900 mPas; or
[0037] The aqueous emulsion is selected from aqueous acrylic resin emulsion, and preferably the aqueous acrylic resin emulsion has a latex particle size of 0.05-0.3 μm and a solid content of 45%-51%, preferably 49-51%.
[0038] The defoamer is selected from one or more of water-based mineral oil defoamer and organosilicon defoamer.
[0039] The dispersant is an anionic dispersant, such as sodium polyacrylate, sodium polycarboxylate, and ammonium polycarboxylate dispersants, with an effective content of ≥35%, preferably ≥43%, and a kinematic viscosity of 300-700 mPas, preferably 350-500 mPas.
[0040] The pH regulator is selected from alcohol amine compounds, such as primary, secondary or tertiary C 1-9 Alkanolamine, pH value 7-9.
[0041] The thickener is selected from cellulose, such as hydroxyethyl cellulose, methyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose; preferably, the thickener is hydroxyethyl cellulose, and its viscosity is 1200-3000cps, such as 1500-2500cps.
[0042] Alternatively, the thickener is selected from one or more associative polymer thickeners.
[0043] The fungicide is an isothiazolinone fungicide, such as 1,2-benzisothiazolin-3-one (BIT), 2-octyl-4-isothiazolin-3-one (OIT), 2-methyl-4-isothiazolin-3-one (MIT), and 5-chloro-2-methyl-4-isothiazolin-3-one (CMIT).
[0044] The film-forming aid is selected from alcohols, alcohol esters, alcohol ethers, and alcohol ether ester film-forming agents, such as benzyl alcohol, ethylene glycol, propylene glycol, hexylene glycol, alcohol ester dodecahydrate, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, and tripropylene glycol n-butyl ether.
[0045] The intumescent flame retardant is mainly composed of three parts: an acid source, a carbon source and a gas source. The acid source is ammonium polyphosphate surface-modified with an aminosilane coupling agent; the carbon source is one or more of pentaerythritol and polyamide resin; and the gas source is one or more of melamine, glycine and polyamino acid ester.
[0046] In order to achieve a good chemical expansion effect and form a hard carbonized layer under high temperature environment, the above-mentioned intumescent flame retardant has an acid source, a carbon source and a gas source in a mass ratio of acid source: carbon source: gas source = (4-10): (1-3): (1-3). Preferably, the ratio of the three is 3:1:1.
[0047] The refractory filler is selected from one or more of titanium dioxide, kaolin, silica powder, and aluminum hydroxide. Preferably, the refractory filler is a combination of titanium dioxide and aluminum hydroxide, and the mass ratio of the two is (1-4): (4-10).
[0048] The titanium dioxide is rutile titanium dioxide, and the rutile content is ≥93%, preferably ≥98%.
[0049] The aluminum hydroxide has a mesh size of 1000 to 5000 meshes, and an Al2O3 content of ≥50%, preferably ≥63%.
[0050] The zinc oxide is selected from zinc oxide with a content of ≥95%, preferably ≥99.7%.
[0051] The plasticizer is a polyol ester plasticizer, which is composed of C 1-18 diols, polyols, triols and C 2-18 The polyol is ethylene glycol, propylene glycol, butylene glycol, pentanediol; the fatty acid is succinic acid, stearic acid, oleic acid, etc.;
[0052] Alternatively, the plasticizer is trimethylpentanediol, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB) and / or trimethylolpropane.
[0053] The water-based fire retardant coating according to the present invention is a water-based fire retardant coating for cables.
[0054] The present invention also provides a method for preparing the above-mentioned water-based fire retardant coating, which mainly comprises the following steps:
[0055] (1) adding the above-mentioned water, defoamer, dispersant, pH regulator, thickener, and bactericide into a high-speed dispersing device according to a set ratio and dispersing;
[0056] (2) adding the above-mentioned intumescent flame retardant, refractory filler and zinc oxide according to a set ratio to the high-speed dispersing equipment in the above-mentioned step (1), and continuing to disperse to form a slurry;
[0057] (3) Adding the aqueous emulsion and film-forming aid into the slurry obtained in the above step (2) in a set ratio, dispersing them evenly, and preparing a coating.
[0058] According to the preparation method of the present invention, it also includes the following steps:
[0059] (4) Grind the coating obtained in the above step (3) to a required fineness through a grinding device and then package it.
[0060] According to the preparation method of the present invention, the dispersion speed in steps (1), (2) and (3) is set to 700-1200 rpm, and the dispersion time is 7-30 minutes, for example, 10-15 minutes.
[0061] According to the preparation method of the present invention, in step (4), the grinding fineness is less than 90 μm.
[0062] The present invention also provides an application of the water-based fire retardant coating, which is used in the construction industry and electric power, such as fire protection of cables, steel structures, and walls.
[0063] Preferably, the fire retardant coating is used for cable fire protection.
[0064] Beneficial effects of the present invention:
[0065] (1) The present invention provides a water-based fire retardant coating with high bending resistance, high resistance to medium solvents, and high weather resistance. Through the selection of water-based emulsions, the selection and matching of functional additives, and the surface modification of related powder fillers, the fire retardant coating has oil resistance, salt water resistance, moisture and heat resistance, and bending resistance far exceeding the requirements of GB 28374-2012 standard, so as to ensure that the product has a longer service life when used in harsh outdoor environments. The specific performance is as follows:
[0066]
[0067] (2) The raw materials of the water-based fire retardant coating of the present invention are all halogen-free and environmentally friendly materials. The environmental performance of the product meets the requirements of the RoHS2.0 directive. No obvious smoke is generated during combustion. According to SGS testing, the test results of cadmium, lead, mercury, hexavalent chromium, polybrominated biphenyls, polybrominated diphenyl ethers, phthalates, benzyl phthalate, di(2-ethylhexyl) phthalate and diisobutyl phthalate meet the limit requirements of Directive (EU) 2015 / 863 amending Annex II of EU RoHS Directive 2011 / 65 / EU.
[0068] (3) The water-based fire-retardant coating of the present invention forms a hard carbonized layer under high-temperature flames through the synergistic effect between the refractory filler and the intumescent flame retardant. This hard carbonized layer is not only resistant to ablation, but also blocks the transfer of most of the flame heat. At the same time, the intumescent flame retardant produces chemical reaction expansion under high temperature conditions, and a large number of fine micropores are generated inside the product, which reduces the overall thermal conductivity. Compared with domestic products, it has better fire resistance, the carbonized layer is harder and denser, resistant to ablation, and has a higher expansion ratio. The specific comparative test results are as follows:
[0069]
[0070] DETAILED DESCRIPTION
[0071] The technical scheme of the present invention will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection intended by the present invention. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by known methods; the operations performed are all known in the art, or are performed in accordance with the user manual of commercially available products.
[0072] Embodiment 1:
[0073] The raw material components of this embodiment are as follows:
[0074] Deionized water 30 Water-based emulsion 21 Defoaming agent 0.5 Dispersants 0.3 pH Adjuster 0.1 Thickener 0.2 Fungicides 0.1 Plasticizers 1 Film-forming aids 0.8 Ammonium Polyphosphate 20.4 Pentaerythritol 6.8 Melamine 6.8 Titanium dioxide 3 Zinc Oxide 2 Aluminum hydroxide 7
[0075] The vinyl acetate-ethylene copolymer emulsion selected as the aqueous emulsion is VINNAPASEZ 3066 vinyl acetate-ethylene copolymer emulsion commercially available from Wacker Chemicals, which has a vinyl acetate (VA) content of 89% to 95%, a solid content of 54% to 56%, and a viscosity of 2700 to 5900 mPas;
[0076] The aqueous mineral oil defoamer selected as the defoamer is BYK-035 defoamer commercially available from BYK Chemicals, with a solid content of 99%;
[0077] The polymer dispersant of polycarboxylate sodium salt selected in the above dispersant is a commercially available anionic polycarboxylate sodium salt dispersant, K-542 produced by Zhongke Hongtai Company, with an effective content of ≥43% and a kinematic viscosity of 350-500 mPas;
[0078] The alcohol amine compound selected as the pH regulator is AMP95 additive, with a pH value of 7 to 9, which can improve the storage stability and water resistance of the product;
[0079] The thickener is hydroxyethyl cellulose with a viscosity of 1500-2500 cps;
[0080] The fungicide is 2-octyl-4-isothiazoline-3-one;
[0081] The above-mentioned plasticizer is trimethylpentanediol, with a content of ≥99.0%, which can improve the bending resistance of the coating;
[0082] The above-mentioned film-forming aid is alcohol ester twelve, and the content is ≥99.5%;
[0083] The above-mentioned intumescent flame retardant selects ammonium polyphosphate as an acid source, pentaerythritol as a carbon source, and melamine as a gas source, and the ratio between the three is 3:1:1. Here, the ammonium polyphosphate is surface treated with an aminosilane coupling agent to improve its water resistance;
[0084] The titanium dioxide in the above-mentioned is rutile titanium dioxide, and the rutile content is ≥98%, which can cooperate with the above-mentioned intumescent flame retardant to improve the strength of the ablation layer at high temperature;
[0085] The zinc oxide in the above-mentioned invention has a zinc oxide content of ≥ 99.7%;
[0086] The aluminum hydroxide selected in the above has a mesh size of 1000 to 5000 meshes and an Al2O3 content of ≥63%;
[0087] The preparation method of the water-based cable fire retardant coating is as follows:
[0088] (1) Add the above-weighed 30 parts of deionized water, 0.5 parts of defoaming agent, 0.3 parts of dispersant, 0.1 parts of pH regulator, and 0.1 parts of bactericide into a high-speed dispersing device for mixing, and set the dispersing speed to 900 rpm and the dispersing time to 10 to 15 minutes;
[0089] (2) 34 parts of intumescent flame retardant, 3 parts of titanium dioxide, 2 parts of zinc oxide, 8 parts of aluminum hydroxide powder, and 0.2 parts of thickener weighed above are added to a high-speed dispersing device in sequence, the dispersing speed is set to 900 rpm, the dispersing time is 10 to 15 minutes, and the mixture is evenly dispersed to form a slurry;
[0090] (3) 21 parts of the aqueous emulsion and 1 part of the film-forming aid weighed above are added to a high-speed dispersing device in sequence, the dispersing speed is set to 900 rpm, the dispersing time is 30 to 60 minutes, and the coating is evenly dispersed;
[0091] (4) Grinding the coating prepared above to a fineness of less than 90 μm by a three-roll grinding device to obtain the water-based cable fire retardant coating with high bending resistance, high resistance to medium solvents, and high weather resistance.
[0092] Embodiment 2:
[0093] The raw material components of this embodiment are shown in the following table:
[0094] Deionized water 30 Water-based emulsion 21 Defoaming agent 0.5 Dispersants 0.3 pH Adjuster 0.1 Thickener 0.2 Fungicides 0.1 Plasticizers 1 Film-forming aids 0.8 Ammonium Polyphosphate 20.4 Pentaerythritol 6.8 Melamine 6.8 Titanium dioxide 3 Zinc Oxide 2 Aluminum hydroxide 7
[0095] The aqueous acrylic resin emulsion selected in the above aqueous emulsion is Acronal ECO 6258 commercially available from BASF, with a latex particle size of 0.15 μm and a solid content of 49% to 51%;
[0096] The above-mentioned defoamer selected as the silicone defoamer is BYK-035 defoamer commercially available from BYK Chemicals;
[0097] The polymer dispersant of polycarboxylate sodium salt selected in the above dispersant is an anionic polycarboxylate sodium salt dispersant, which is K-542 produced by Zhongke Hongtai Company, with an effective content of ≥43% and a kinematic viscosity of 350-500 mPas;
[0098] The PH regulator selected from the alcohol amine compound is a commercially available AMP95 additive with a PH value of 7 to 9, which can improve the storage stability and water resistance of the product;
[0099] The above-mentioned thickener is an associative polymer thickener, which is a commercially available TT-40 polymer thickener from Xinyi Synthetic Formula;
[0100] The fungicide is 2-octyl-4-isothiazoline-3-one;
[0101] The above-mentioned plasticizer is trimethylpentanediol, with a content of ≥99.0%, which can improve the bending resistance of the coating;
[0102] The above-mentioned film-forming aid is alcohol ester twelve, and the content is ≥99.5%;
[0103] The above-mentioned intumescent flame retardant selects ammonium polyphosphate as an acid source, pentaerythritol as a carbon source, and melamine as a gas source, and the ratio between the three is 3:1:1. Here, the ammonium polyphosphate is surface treated with an aminosilane coupling agent, and the SCA-A10T monoaminosilane coupling agent produced by Nanjing Nengde Company is selected to improve its water resistance.
[0104] The titanium dioxide in the above-mentioned is rutile titanium dioxide, and the rutile content is ≥98%, which can cooperate with the above-mentioned intumescent flame retardant to improve the strength of the ablation layer at high temperature;
[0105] The zinc oxide in the above-mentioned invention has a zinc oxide content of ≥ 99.7%;
[0106] The aluminum hydroxide selected above has a mesh size of 1000 to 5000 meshes and an Al2O3 content of ≥63%.
[0107] The preparation method of the water-based cable fire retardant coating is as follows:
[0108] (1) Add the above-weighed 30 parts of deionized water, 0.5 parts of defoaming agent, 0.3 parts of dispersant, 0.1 parts of pH regulator, and 0.1 parts of bactericide into a high-speed dispersing device for mixing, and set the dispersing speed to 900 rpm and the dispersing time to 10 to 15 minutes;
[0109] (2) 34 parts of intumescent flame retardant, 3 parts of titanium dioxide, 2 parts of zinc oxide, 8 parts of aluminum hydroxide powder, and 0.2 parts of thickener weighed above are added to a high-speed dispersing device in sequence, the dispersing speed is set to 900 rpm, the dispersing time is 10 to 15 minutes, and the mixture is evenly dispersed to form a slurry;
[0110] (3) 21 parts of the aqueous emulsion and 1 part of the film-forming aid weighed above are added to a high-speed dispersing device in sequence, the dispersing speed is set to 900 rpm, the dispersing time is 30 to 60 minutes, and the coating is evenly dispersed;
[0111] (4) Grinding the coating prepared above to a fineness of less than 90 μm by a three-roll grinding device to obtain the water-based cable fire retardant coating with high bending resistance, high resistance to medium solvents, and high weather resistance.
[0112] Comparative Example 1:
[0113] Compared with Example 1, the difference between this comparative example and Example 1 is that a vinyl acetate-ethylene copolymer emulsion with a conventional VA content is used, which is characterized by a vinyl acetate (VA) content of 78% to 82%, a solid content of ≥55%, and a viscosity of 2000 to 4000 mPas, and the strength and expansion ratio of the ablation layer at high temperature are compared.
[0114] Comparative Example 2:
[0115] Compared with Example 1, the difference between this comparative example is that the intumescent flame retardant in the components selects ammonium polyphosphate as the acid source, pentaerythritol as the carbon source, and melamine as the gas source, and the ratio between the three is 1:1:1. The strength and expansion ratio of the ablation layer at high temperature are compared.
[0116] Comparative Example 3:
[0117] Compared with Example 1, the difference between this comparative example is that the intumescent flame retardant in the components selects ammonium polyphosphate as the acid source, pentaerythritol as the carbon source, and melamine as the gas source, and the ratio between the three is 6:1:1. The strength and expansion ratio of the ablation layer at high temperature are compared.
[0118] Comparative Example 4:
[0119] The difference between this comparative example and Example 1 is that non-rutile titanium dioxide is used, and anatase titanium dioxide is selected to compare the strength of the ablation layer at high temperature.
[0120] Comparative Example 5:
[0121] Compared with Example 1, this comparative example differs in that a vinyl acetate-ethylene copolymer emulsion with a conventional VA content is used, which is characterized by a vinyl acetate (VA) content of 78% to 82%, a solid content of ≥55%, a viscosity of 2000 to 4000 mPas, and no plasticizer is added to compare the flexural resistance of the final coating.
[0122] Comparative Example 6:
[0123] Compared with Example 1, this comparative example differs in that sodium hydroxide solution is used as the pH regulator and ammonium polyphosphate without surface treatment is used to compare the salt water resistance, oil resistance, and moisture and heat resistance of the final coating.
[0124] Comparative Example 7:
[0125] This comparative example is compared with Example 2. The difference is that the latex particle size of the conventional water-based acrylic resin emulsion is 50-0100 μm, and the solid content is 45%±1%, and the strength and expansion ratio of the ablation layer of products with different latex particle sizes at high temperature are compared.
[0126] Comparative Example 8:
[0127] Compared with Example 2, the difference between this comparative example and Example 2 is that the latex particle size of the selected aqueous acrylic resin emulsion is 0.1-0.2 μm, the solid content is 45%±1%, and no plasticizer is added, and the bending resistance of the final coating is compared.
[0128] Comparative Example 9:
[0129] Compared with Example 2, this comparative example uses sodium hydroxide solution as a pH regulator and uses ammonium polyphosphate without surface treatment to compare the salt water resistance, oil resistance, and moisture and heat resistance of the final coating. The following table shows the comparative test items and results:
[0130]
[0131]
[0132] In addition, the present invention also compares the carbonized layer strength and expansion ratio of the comparative example and the embodiment. The coating is evenly coated on the cable surface or steel plate substrate with a coating thickness of 1.0±0.1mm. After the coating is completely dry, a spray gun with a flame temperature of >750℃ is used for ablation for more than 10 minutes. After the ablation is completed, the strength of the ablation layer is observed and the expansion ratio is measured. The following are the experimental results:
[0133]
[0134] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A water-based fire retardant coating, made from the following raw material components:
2. The water-based fire retardant coating according to claim 1, which is made from the following raw material components: Refractory filler 6-10 parts Zinc oxide 1-5 parts Plasticizer 0.1 to 2 parts.
3. The water-based fire retardant coating according to claim 1 or 2, wherein: The water is deionized water; and / or, The aqueous emulsion is selected from vinyl acetate-ethylene copolymer emulsion or aqueous acrylic resin emulsion; and / or, The defoamer is selected from one or more of water-based mineral oil defoamer and silicone defoamer; and / or, The dispersant is an anionic dispersant, such as sodium polyacrylate, sodium polycarboxylate, or ammonium polycarboxylate dispersants; and / or, The pH regulator is selected from alcohol amine compounds, such as primary, secondary or tertiary C 1-9 Alkanolamine, pH 7 to 9; and / or The thickener is selected from cellulose, such as hydroxyethyl cellulose, methyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose, or one or more associative polymer thickeners; and / or, The fungicide is an isothiazolinone fungicide, such as 1,2-benzisothiazolin-3-one (BIT), 2-octyl-4-isothiazolin-3-one (OIT), 2-methyl-4-isothiazolin-3-one (MIT), 5-chloro-2-methyl-4-isothiazolin-3-one (CMIT); and / or, The film-forming aid is selected from alcohols, alcohol esters, alcohol ethers, and alcohol ether ester film-forming agents, such as benzyl alcohol, ethylene glycol, propylene glycol, hexylene glycol, alcohol ester dodecahydrate, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, and tripropylene glycol n-butyl ether; and / or, The intumescent flame retardant is mainly composed of an acid source, a carbon source and a gas source, wherein the acid source is ammonium polyphosphate surface-modified with an aminosilane coupling agent; the carbon source is one or more of pentaerythritol and polyamide resin; the gas source is one or more of melamine, glycine and polyamino acid ester; and / or, The refractory filler is selected from one or more of titanium dioxide, kaolin, silica powder, and aluminum hydroxide; and / or, The titanium dioxide is rutile titanium dioxide, and the rutile content is ≥93%, preferably ≥98%; and / or, The aluminum hydroxide has a mesh size of 1000 to 5000 meshes and an Al2O3 content of ≥50%, preferably ≥63%; and / or, The zinc oxide is selected from zinc oxide with a content of ≥95%, preferably ≥99.7%; and / or, The plasticizer is a polyol ester plasticizer, which is composed of C 1-18 diols, polyols, triols and C 2-18 The polyol is ethylene glycol, propylene glycol, butylene glycol, pentanediol; the fatty acid is succinic acid, stearic acid, oleic acid; or the plasticizer is trimethylpentanediol, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB) and / or trimethylolpropane.
4. The water-based fire retardant coating according to claim 3, wherein: The vinyl acetate-ethylene copolymer emulsion has a vinyl acetate (VA) content of 89% to 95%, a solid content of 54% to 56%, and a viscosity of 2700 to 5900 mPas; or, the aqueous acrylic resin emulsion has a latex particle size of 0.05 to 0.3 μm and a solid content of 45% to 51%, preferably 49-51%; and / or, The polyacrylic acid sodium salt, polycarboxylic acid sodium salt, polycarboxylic acid ammonium salt dispersant has an effective content of ≥35%, preferably ≥43%, and a kinematic viscosity of 300-700 mPas, preferably 350-500 mPas; and / or, The thickener is hydroxyethyl cellulose, and its viscosity is 1200-3000cps, such as 1500-2500cps; and / or, The thickener is hydroxyethyl cellulose, and its viscosity is 1200-3000cps, such as 1500-2500cps; and / or, The mass ratio of the acid source, carbon source and gas source in the intumescent flame retardant is acid source: carbon source: gas source = (4-10): (1-3): (1-3), preferably, the ratio is 3:1:1; and / or, The refractory filler is a combination of titanium dioxide and aluminum hydroxide, and the mass ratio of the two is (1-4): (4-10).
5. The water-based fire retardant coating according to any one of claims 1 to 2, which is a water-based cable fire retardant coating.
6. The method for preparing the water-based fire retardant coating according to claim 1 mainly comprises the following steps: (1) adding the above-mentioned water, defoamer, dispersant, pH regulator, thickener, and bactericide into a high-speed dispersing device according to a set ratio and dispersing; (2) adding the above-mentioned intumescent flame retardant, refractory filler and zinc oxide according to a set ratio to the high-speed dispersing equipment in the above-mentioned step (1), and continuing to disperse to form a slurry; (3) Adding the aqueous emulsion and film-forming aid into the slurry obtained in the above step (2) in a set ratio, dispersing them evenly, and preparing a coating.
7. The preparation method according to claim 6, further comprising the steps of: (4) Grind the coating obtained in the above step (3) to a required fineness through a grinding device and then package it.
8. The preparation method according to any one of claims 6 to 7, wherein the dispersion in steps (1), (2) and (3) is performed at a dispersion speed of 700 to 1200 rpm and a dispersion time of 7 to 30 minutes; In the step (4), the grinding fineness is less than 90 μm.
9. Application of the water-based fire retardant coating according to any one of claims 1 to 5, which is used in the construction industry and electric power, such as fire protection of cables, steel structures and walls.
10. The use according to claim 9, wherein the fire retardant coating is used for fire protection of cables.
Citation Information
Patent Citations
Method for preparing aminosilane coupling agent modifying ammonium polyphosphate
CN101235221A
Waterproof efficient intumescent fire retardant coating
CN102911566A
Styrene-acrylic water-based intumescent fireproof coating and preparation method thereof
CN108485350A
Self-cleaning and fireproof multifunctional coating for steel structure and preparation method of self-cleaning and fireproof multifunctional coating
CN110343457A
Environment-friendly and halogen-free water-based cable fireproof coating and preparation method thereof
CN111363427A
Cited By
Environment-friendly water-based anti-corrosion anti-crack cable fireproof coating and preparation method thereof
CN122103978A